Forest Diversity of Nepal’s Protected Areas in the Mountains - Shrestha, Tirtha Bahadur (Himalayan Review, 2011)
Available with fulltext. Key words: Terrestrial ecosystem; Protected area; Phytogeographic; Bio-diversity The Himalayan Review Nepal Geographical Society Vol. XXXII 2001 Page:25-29 Uploaded date: 7 June, 2011